2008
DOI: 10.1136/bjsm.2007.044057
|View full text |Cite
|
Sign up to set email alerts
|

Are the take-off and landing phase dynamics of the volleyball spike jump related to patellar tendinopathy?

Abstract: Smaller joint flexion during the first part of landing impact , and higher rate of knee moment development during the eccentric phases of the spike-jump landing sequence, together with higher knee angular velocities, might be risk factors in the development of patellar tendinopathy in volleyball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
94
1
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(111 citation statements)
references
References 21 publications
6
94
1
6
Order By: Relevance
“…20,21 A number of descriptive biomechanical studies have also established associations between lower extremity movement dynamics and patellar tendinopathy in elite athletes, particularly volleyball players. 6,7,20,21,23,24 Richards and colleagues 23,24 linked complex ankle and knee joint moments, rates of moment development, and vertical ground reaction forces during sport-specific takeoff and landing movements to the presence of acute tendinopathy in internationally competitive male players. Recently, Bisseling et al 6,7 have reported a biomechanical distinction between competitive male players with no history of patellar tendinopathy, currently asymptomatic players with a prior history, and presently symptomatic players during both drop jumps and sport-specific movements.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…20,21 A number of descriptive biomechanical studies have also established associations between lower extremity movement dynamics and patellar tendinopathy in elite athletes, particularly volleyball players. 6,7,20,21,23,24 Richards and colleagues 23,24 linked complex ankle and knee joint moments, rates of moment development, and vertical ground reaction forces during sport-specific takeoff and landing movements to the presence of acute tendinopathy in internationally competitive male players. Recently, Bisseling et al 6,7 have reported a biomechanical distinction between competitive male players with no history of patellar tendinopathy, currently asymptomatic players with a prior history, and presently symptomatic players during both drop jumps and sport-specific movements.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…6,7,20,21,23,24 Richards and colleagues 23,24 linked complex ankle and knee joint moments, rates of moment development, and vertical ground reaction forces during sport-specific takeoff and landing movements to the presence of acute tendinopathy in internationally competitive male players. Recently, Bisseling et al 6,7 have reported a biomechanical distinction between competitive male players with no history of patellar tendinopathy, currently asymptomatic players with a prior history, and presently symptomatic players during both drop jumps and sport-specific movements. These studies concluded, in part, that stiffer lower extremity dynamic patterns employing lesser joint range of motion and higher rates of knee extensor moment development may be predictive of pathology, particularly during eccentric countermovements.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos datos confirman las sospechas de los profesionales del judo a cerca de los riesgos que puede suponer la realización de esta técnica en determinados deportistas, y justifican los cambios que se han producido a lo largo del tiempo en los reglamentos. Los impactos registrados se encuentran al nivel de los de la caída de un remate en voleibol (4.25 PC, Bisseling et al, 2008) o de la caída tras un rebote en baloncesto (7.1 PC, Valiant y Cavanagh, 1985). Podemos afirmar que el impacto producido por los judokas al realizar la técnica seoiotoshi es considerable, más si entendemos que en las tareas anteriormente descritas, los deportistas producen ese impacto al contactar con el suelo sobre las plantas de los pies calzados, mientras que en el caso de la técnica seoiotoshi estos se producen en primera instancia sobre las rodillas.…”
Section: Discusión Y Conclusionesunclassified
“…Whereas increased knee valgus has been associated with the risk of ACL rupture, 8 investigators have also related decreased sagittal-plane hip and knee movement with ACL rupture, 8 patellofemoral pain, 6 and patellar tendinopathy. 5,7,9 Consequently, relying solely on frontal-plane knee alignment during jumping and landing may underestimate the level of risk associated with these functional tasks.…”
mentioning
confidence: 99%